INCREASING LEARNING OUTCOMES OF SOCIAL STUDIES GRADE 8TH OF PURWOKERTO 8TH STATE JUNIOR HIGH SCHOOL WITH CONTEXTUAL LEARNING IN THE ERA OF NEW ADAPTATION - Rudhi Julianto (Sosio-Didaktika: Social Science Education Journal, 2021)
AbstractThis study aims to determine whether contextual learning can improve learning independence, students 'short essay writing skills, and students' formative test scores. During the Covid-19 pandemic contextual learning provided meaningful activities for students with independent learning. The elements of contextual approach learning applied in distance learning are self-study note-making, independent learning, and authentic assessment in the form of essay writing skills. Students' understanding of the subject matter with independent study notes can help students write short essays about the material that has been studied. Self-study notes and short essays are authentic assessments. The research method used is action research carried out in 2 research cycles. Based on the data from the first cycle, it was obtained 80% learning participation, 58% independent learning note assignment collection, and 60% essay writing. The value of independent study notes is 79, essay score is 77, and formative test is 80. Based on cycle II data, it is found that learning participation is 88%, collection of independent study notes assignments is 78%, and essay writing is 80%. The value of independent study notes is 86, essay score is 84, and formative test is 88. The discussion of this research can be seen in the differences in data in cycle I and cycle II which have increased even though there is a decrease in learning participation between pre-cycle and cycle 1. Based on the data and analysis carried out, it can be concluded that contextual learning can improve student learning achievement indicated by an increase in the value of independent study notes, essay writing skills and students' formative tests.Keywords: contextual learning, independent learning, writing skills